Comparison of Bactericidal Properties of ZnO Nanoparticles Obtained By Two Synthesis Methods - (:unkn) unknown (Avestia Publishing, 2024)
The potential bactericidal properties of nanosized zinc oxide (ZnO) make this semiconductor suitable for medical and pharmaceutical applications. In this article we present two methods of synthesis of ZnO nanoparticles (Nps-ZnO): chemical precipitation a...
Keywords: Nanopartículas de ZnO; Propiedades bactericidas